Fatigue failure processes in pb-free solder joints using continuum damage and cohesive zone models - Shaffiar, Norhashimah; Yamin, A.F.M.; Loh, W.K.; Tamin, M.N. (2012)
The mechanics of failure in a solder joint under cyclic mechanical loading is quantified and described in this paper. It is postulated that fatigue failure of the solder joint occurs through simultaneous competitive mechanisms of cyclic damage processes occurring through the bulk solder and across solder/IMC interface. Progressive damage in the bulk solder joint is described using continuum damage model while cohesive zone model simulates the fracture process of the solder/IMC interface. For this purpose, a single-solder joint assembly with Sn-4Ag-0.5Cu (SAC405) solder and SAC405/Cu6Sn5 interface is modeled using finite element (FE) method. Unified inelastic strain model (Anand’s) with optimized parameter values for SAC405 solder represents the strain rate-dependent response of the solder. Cyclic plastic work-based phenomenological continuum damage model and cyclic stress- and energy-based cohesive zone model are employed to simulate damage response of the bulk solder and solder/IMC interface, respectively. Cyclic displacement loading (Δδ = 0.003 mm, R = 0) is prescribed to the edge of the “rigid” tool. Results show that the solder/IMC interface fatigue cracking dominates the fracture process. Fatigue crack initiated at the leading edge of the solder/IMC interface on the tool side of the assembly after accumulated 18 fatigue cycles. Simultaneously, inelastic strain accumulates at the critical material point with a decreasing rate. The predicted bending stress with opposing tensile and compressive stress region shall favor shear-driven fatigue crack diagonally across the bulk solder.